Eco-conscious potentiometric sensing: a multiwalled carbon nanotube-based platform for tulathromycin monitoring in livestock products - Omnia G. Hussein; Hany H. Monir; Hala E. Zaazaa; Maha M. Galal (BMC Chemistry, 2024)
Abstract Tulathromycin (TUL) is a widely used veterinary antibiotic for treating bovine and porcine respiratory infections. Consuming animal-derived food contaminated with this medication may jeopardize human health. This work adopted the first portable potentiometric platform for direct TUL sensing in pharmaceutical and food products. The sensor employed a plasticized PVC membrane on a glassy carbon electrode doped with calix[6]arene and multi-walled carbon nanotubes (MWCNT) in a single solid contact layer for selective binding and signal stability. Characterization via scanning electron microscopy (SEM) and Fourier transform infrared spectroscopy (FTIR) confirmed the material’s integrity. The MWCNT-based sensor produced a stable Nernstian response (1.0 × 10−7 to 1.0 × 10−3 M) and a limit of detection (LOD) of 9.76 × 10–8 M with instantaneous response (8 ± 2 s). IUPAC validation revealed high selectivity for TUL against interfering ions, minimal drift (0.6 mV/h), and functionality over a broad pH range (2.0–7.0), allowing direct application to dosage form, spiked milk, and liver samples. Eco-Scale, AGREE, and Whiteness assessment proved the method's ecological sustainability, economic viability, and practical feasibility, surpassing traditional approaches. Graphical Abstract